The fog of war eleven lessons from the life of Robert S. McNamara - Morris, Errol; Williams, Michael, 1957-; Ahlberg, Julie Bilson; McNamara, Robert S., 1916-; Glass, Philip; @Radical.media (Firm); Globe Department Store (Firm); SenArt Films (Firm); Columbia TriStar Home Entertainment (Firm); Sony Pictures Classics (Firm) (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
The story of American politics and military policies as seen through the eyes of the former Secretary of Defense, under President Kennedy and President Johnson, Robert S. McNamara. McNamara is a controversial and influential political figure. He offers a candid journey through some of the most seminal events in contemporary American history. He offers insights into the 1945 fire bombing of Tokyo, the Cuban Missile Crisis, and the effects of the Vietnam War.
DVD format.
English language track with optional subtitles in French, Portuguese, Spanish or Japanese.
Closed-captioned.
Directors of photography, Peter Donahue, Bob Chappell ; editors, Karen Schmeer, Doug Abel, Chyld King ; original music, Philip Glass.
Originally released as a motion picture in 2003.
Anamorphic widescreen (1.78:1); Dolby digital 5.1.
Keywords: McNamara, Robert S., -- 1916-; McNamara, Robert S., -- 1916- -- Interviews; United States -- History -- 1945-; United States -- Military policy; United States -- Military relations; United States -- Politics and government -- 1945-1989.; Tokyo (Japan) -- History -- Bombardment, 1944-1945.; Cuban Missile Crisis, 1962.; Vietnam War, 1961-1975.; McNamara, Robert S., -- 1916-; McNamara, Robert S., -- 1916- -- Interviews; United States -- History -- 1945-; Documentary films; Video recordings for the hearing impaired